Synthesis and Characterization of Soft Magnetic Materials NixZn1-xFe2O4 (x = 0,2 – 0,8) Lombok Iron Sand with Co-precipitation Method - Asri, Nining S (Journal of Technomaterial Physics, 2021)
The synthesis of soft magnetic NixZn1-xFe2O4 with variations in composition (x = 0,2 – 0,8) by the co-precipitation method has been carried out. The research objective was to determine the effect of x variation on the crystal structure, microstructure, magnetic properties, and density. The samples were characterized by their crystal structure using XRD, microstructure using FE-SEM, magnetic properties using VSM, and physical properties (True Density). The XRD analysis results obtained two phases, the major phase is nickel-zinc ferrite, and Fe2O3 shows as the minor phase. The crystal size increased and the lattice parameters decreased with the increase in nickel content. The results of FE-SEM analysis at x = 0.2 are spherical in shape with an average particle size found about 47.07 nm. The results of VSM analysis showed that the increase in nickel content, the higher the magnetization saturation value, and the super-paramagnetic properties of all samples obtained. The results of the analysis of physical properties show that true density decreases with an increase of nickel content in each sample.